Study on the Variation in Shock Characteristics in a TNT-Based Shock Tube Under Different Experimental Conditions - Youngbeom Kwon; Yoonkeon Kim; Jongyil Park; Kyoungmin Kim (Applied Sciences)
In open-air explosion experiments, the measured blast pressure characteristics often show high Coefficients of Variation (COV), causing reproducibility issues. Shock tubes can address this problem. They consist of a driver section, where the shock is generated, and a driven section, where it is transmitted. The shock can be produced using either gas or high explosives (HEs). The intensity of gas-generated shocks are limited due to the driver section’s size, making HE-based shock tubes more suitable for replacing open-field detonation tests. This study derived experimental conditions for an HE-based shock tube to replicate the pressure characteristics from open-air experiments. Conditions include the sealed status of the driver section, TNT location and amount, expansion tube presence, and target location. When TNT was centered at the driver section and the driver section was sealed, reflections caused the peak pressure to occur twice, which is unsuitable for target loading. The COV values of reflected pressures at different locations of target were high without target contact but dropped significantly with contact, showing that target contact with the shock tube is necessary for uniform pressure generation. Additionally, it was confirmed that using the expansion section also resulted in low COV values for both reproducibility and uniform pressure.